Impacts of the 2019 coronavirus (COVID-19) on the environment - Toribio Román, Fernando Martin (2022)
Introduction: COVID-19 brought effects at a general level, one of them is in the environment for which its study is necessary to propose solutions to this pandemic. The objective is to determine the effects that COVID-19 has brought to the environment, through a descriptive study and documentary review. Obtaining consequences in the air, soil and water spheres that generate visible impacts on society, the economy and mainly on the environment. In conclusion, there are positive environmental effects, such as the improvement of air quality; and negative, such as the high contamination by medical and domestic waste, the latter being the most alarming. To this end, reflections and proposals for measures to counteract them are proposed.